Co-management of Reservoir Fisheries for Sustainable Livelihoods: Insights for Fishery Managers and Extension Professionals from Field Studies in India - Tyagi, L.K.; Bisht, A.S.; Pal, Amar (Indian Journal of Extension Education, 2015)
Reservoirs hold tremendous potential for inland fisheries development and offer ample scope for fish yield optimization  through adoption of appropriate management measures. H owever, there are several socio-economic issues involved in  their management as communities displaced due to creation of these reservoirs depend upon them for earning  livelihoods.Reservoirs hold tremendous potential for inland fisheries development and offer ample scope for fish yield  optimization through adoption of appropriate management measures. Governance and management pattern of these  reservoirs varies in different states of India and faces several challenges including the twin pressures, to increase the  production and productivity, and ensure sustainable livelihoods for communities dependent upon these resources. The  present paper while discussing these issues elaborates upon the co-management approach to address them. Citing  synthesized overall summary of the major findings of the field studies done in Northern, Central and Eastern India, the  paper elaborates upon the performance of fishing cooperative societies in co-management and conservation of reservoir  fishery resources and roles played by various stakeholders and their linkages in this endeavor. The paper is based on  review of literature, secondary data from various records, and primary data gathered and detail interactions had with  several stakeholders during field studies in four states of India namely, Madhya Pradesh, Himachal Pradesh, Uttar Pradesh  and Orissa covering 57 fishing cooperative societies and 875 respondents. The findings indicated that local communities  and their organizations (fishing cooperative societies/federations) can play important role in collective management of  reservoir fisheries under the situations where some of the facilitating conditions for promoting collective action are  present. The paper concludes that governance and management of reservoir fisheries need to be viewed in light of the  recent developments and empirical evidences made available by the social scientists in natural resource management.  There is tremendous scope for innovation in their governance. Lessons drawn from successes achieved in various forms of  co-management fisheries resources, such as reported here and elsewhere across the globe, need to be incorporated in  devising policies and programmes for management of reservoir fisheries. The field of fisheries management and  conservation presents enormous possibilities for the extension professionals to broaden their canvas and contribute policy  oriented studies to help the fisheries managers and policy makers in further improving the sector.
Keywords: Reservoir fisheries; co-management; fishing cooperative societies; sustainable livelihoods